Heterosis and combining ability of seed protein, yield and yield components in long bean - Mak, C.; Yap, T. C. (Crop Science Society of America, 1977)
Seven cultivars of long bean (Vigna sesquipedalis Fruw.) were crossed in dialIel; the parents and F,'s were evaluated in the field in 1973. Out of 42 hybrids, only three had seed protein contents significantly greater than the higher parent values. A majority of the hy- brids yielded more than the higher parent. The amount of heterosis ranged from 40.7% below to 63.2% above the higher parent values. O( these, however, only two were statisticaJly significant. Among the yield compo· nents, pods per I?la~t showed the greatest amount of heterosis. Heterosts In seeds per pod, pod length, and seed weight were relatively low. Both general combining ability (GCA) and specific combining ability (SC~) were important (or alI traits measured except pod Yield where only GCA was signlfi- cant. Good combiners (or pod yield were poor combiners [or seed protein content and the SCA effects for yield de- pended mainly on the SCA values of the yield components.